Fatty acid signaling: the new function of intracellular lipases - Papackova, Zuzana; Cahova, Monika (International journal of molecular sciences, 2015)
Until recently, intracellular triacylglycerols (TAG) stored in the form of cytoplasmic lipid droplets have been considered to be only passive "energy conserves". Nevertheless, degradation of TAG gives rise to a pleiotropic spectrum of bioactive intermediates, which may function as potent co-factors of transcription factors or enzymes and contribute to the regulation of numerous cellular processes. From this point of view, the process of lipolysis not only provides energy-rich equivalents but also acquires a new regulatory function. In this review, we will concentrate on the role that fatty acids liberated from intracellular TAG stores play as signaling molecules. The first part provides an overview of the transcription factors, which are regulated by fatty acids derived from intracellular stores. The second part is devoted to the role of fatty acid signaling in different organs/tissues. The specific contribution of free fatty acids released by particular lipases, hormone-sensitive lipase, adipose triacylglycerol lipase and lysosomal lipase will also be discussed.
Keywords: Lipase; signální transdukce; Signal Transduction; Organ Specificity; transkripční faktory; mastné kyseliny; Animals; Humans; lidé; orgánová specificita; Transcription Factors; zvířata; Fatty Acids; lipasa